New opportunities in management of patients with retinopathy prematurity (literature review and analysis of own data) - L. A. Katargina; E. N. Demchenko (Российский офтальмологический журнал)
Insufficient effectiveness of laser coagulation of the avascular retinal areas in retinopathy of prematurity (ROP) plus-disease in zone I and aggressive posterior retinopathy of prematurity (APROP) requires new treatment approaches, based on the regulation of retinal angiogenesis and anti-VEGF drugs use. The BEAT-RAP study, which was the first major randomized study of anti-VEGF therapy in ROP, revealed a higher effectiveness of bevacizumab compared to retinal laser coagulation in stage 3 plus-disease of zone I. A prospective randomized trial, RAINBOW, demonstrated the effectiveness of ranibizumab in plus-disease stages 1, 2 and 3 in zone I and stage 3 in zone II and in APROP, so that the drug may be recommended for use in children with ROP. The demonstrated high effect of anti-VEGF therapy in ROP is consistent with our own data. Anti-VEGF therapy opens up new possibilities in the treatment of a particular class of ROP forms. The advantages of anti-VEGF therapy include higher clinical effectiveness of treatment of ROP type I with localization in the posterior pole (I and posterior II zone), absence of "blockage" of the peripheral retina, lower frequency of myopia development and degree, relative fastness of the procedure, the acceptability for patients whose fundus is difficult to visualize, and somatically burdened patients who are contraindicated for prolonged anesthesia used for retinal laser coagulation. When using anti-VEGF drugs in the post-threshold stages of the disease, one should take account of an increased risk of proliferation progression and retinal detachment development. Premature infants with retinopathy regression after anti-VEGF therapy require a longer duration of regular and frequent follow-up (up to 70 weeks of postmenstrual age) due to the risk of relapse and extraretinal proliferation in future.